2017
DOI: 10.2147/jmdh.s138815
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a diabetes mellitus pictorial diary handbook program for middle-aged and elderly type 2 diabetes mellitus patients: a quasi-experimental study at Taladnoi Primary Care Unit, Saraburi, Thailand

Abstract: AimThe research question is “How does a diabetes mellitus (DM) pictorial diary handbook (PDHB) affect the knowledge, practice, and HbA1c among patients with DM type 2?” The aim of this study was to evaluate the effect of a PDHB program among middle-aged and elderly patients with DM type 2 in primary care units in Thailand.Patients and methodsA quasi-experimental study design was applied. DM type 2 patients were recruited in the PDHB program by a simple random sampling method. The 3-month program consisted of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…In Thailand, for example, brief group cognitive behavioral therapy and pictorial diary handbook programs have been shown to be effective for patients with T2DM. 47 , 48 This continuous support for patients with T2DM between district hospitals and PCUs could be effective to maintain their health and healthy lifestyles, including PA.…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, for example, brief group cognitive behavioral therapy and pictorial diary handbook programs have been shown to be effective for patients with T2DM. 47 , 48 This continuous support for patients with T2DM between district hospitals and PCUs could be effective to maintain their health and healthy lifestyles, including PA.…”
Section: Discussionmentioning
confidence: 99%
“…Second, glycosylated hemoglobin >9% indicates persistent high blood sugar. There will be complications such as diabetic nephropathy, arteriosclerosis and cataract in this case, and it is also a high-risk factor for myocardial infarction and stroke death (7)(8). Next, the detection of glycosylated hemoglobin can serve as guidance for protocol adjustment.…”
Section: Methodsmentioning
confidence: 99%
“…Other clinical outcomes reported to be expected in the patient were controlled blood pressure (22,26,(30)(31)(32)(33)(34)(35), controlled FBG (34,36), body mass index (BMI) (26,30,31,34,35); lowdensity lipoprotein (LDL) (22,36), high-density lipoprotein (HDL) (22), and total cholesterol (31). Some studies have also reported secondary outcomes, including patients' knowledge (20,21,24,30,34,37,38), self-efficacy (21,22,24,34,36,(39)(40)(41), habits (20,42,43), physical activity (22,24,34,40,41), ability to follow the diet (20,22,34,44,45), smoking (21,…”
Section: Resultsmentioning
confidence: 99%
“…Other clinical outcomes reported to be expected in the patient were controlled blood pressure ( 22 , 26 , 30 - 35 ), controlled FBG ( 34 , 36 ), body mass index (BMI) ( 26 , 30 , 31 , 34 , 35 ); low-density lipoprotein (LDL) ( 22 , 36 ), high-density lipoprotein (HDL) ( 22 ), and total cholesterol ( 31 ). Some studies have also reported secondary outcomes, including patients’ knowledge ( 20 , 21 , 24 , 30 , 34 , 37 , 38 ), self-efficacy ( 21 , 22 , 24 , 34 , 36 , 39 - 41 ), habits ( 20 , 42 , 43 ), physical activity ( 22 , 24 , 34 , 40 , 41 ), ability to follow the diet ( 20 , 22 , 34 , 44 , 45 ), smoking ( 21 , 45 ), changes in medical treatment ( 31 , 35 , 42 , 44 , 46 ), self-management support ( 38 , 44 , 47 - 49 ), waist circumference ( 30 - 32 ), and healthy behavior ( 20 , 21 , 2...…”
Section: Resultsmentioning
confidence: 99%